Bioactive compounds in the algae of Kappaphycus alvarezii from Belang waters, Southeast Minahasa Regency - Asthisa, Dias; Mantiri, Desy M.H.; Sumilat, Deiske A.; Rompas, Rizal M.; Sinjal, Annita Ch.; Mantiri, Rose O.S.E. (Universitas Sam Ratulangi, 2021)
Algae Kappaphycus alvarezii is one of the leading commodities from fisheries and marine sectors in Indonesia. This algae species has many benefits in the fields of marine biology, chemistry, pharmacy, and pharmacology, as well as an excellent nutritional content for health. It is cultivated in the coastal waters of Minahasan Peninsula, especially in Buku Village, Belang District, Southeast Minahasa Regency. This study was carried out to analyze bioactive compound in the algae. Samples of 2-weeks old were taken directly from the cultivation area. Screening test was done qualitatively while an advanced test was done using LC-HRMS method. The results showed 4 bioactive compounds detected in the sample, they are alkaloids, tannins/phenolics, saponins, and flavonoids. From the advanced test, it was found 10 major compounds in the sample, i.e. (2-ethylhexyl) phthalate, phthalic acid, D-(+)-proline, maraniol, stigmatellin Y, Pentyl isopentyl phthalate, methyl thiofentanyl, phenylethanolamine, acetyl hexamethyl tetralin, and fucoxanthin.Indonesian title: Senyawa bioaktif pada alga Kappaphycus alvarezii dari perairan Belang, Kabupaten Minahasa Tenggara